Firm growth and profitability: The role of mobile IT and organizational practices - Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2010)
This study uses a unique survey data from 398 Finnish manufacturing firms to explore how the order of magnitude of mobility and connectivity of a firm's ICT stock in conjunction with various organizational innovation and HRM practices affect the firm's performance. The data suggest that mobile connectivity as such does not significantly contribute to the firm's growth and profitability. However, the empirical results find support for the agency theory based argument: a greater mobility associated with the use of a pertinent economic incentive scheme and a systematic performance monitoring seems to promote the firm's growth. In addition, re-organization of tasks within an organization is implemented most successfully, boosting profitability, when the firm's re-organization strategy incorporates the adoption of mobile, Internet-connected IT stock.
Keywords: L25; M52; M54; O33; 330; ICT use; mobility; connectivity; organizational practices; firm performance